National trends in endovascular therapy for acute ischemic stroke: utilization and outcomes. (23rd August 2019) - Stein, Laura; Tuhrim, Stanley; Fifi, Johanna; Mocco, J; Dhamoon, Mandip
Abstract : Objective: Following widespread acceptance of endovascular therapy (ET) for large vessel occlusion stroke in 2015, we assessed nationwide utilization of revascularization for acute ischemic stroke (AIS). Methods: We utilized the 2013–2016 Healthcare Cost and Utilization Project Nationwide Readmissions Database. We identified AIS admissions, treatment with intravenous thrombolysis (IVT), ET, and vascular risk factors using International Classification of Disease Clinical Modification codes. Main predictor of outcome was the time period of index admission ('pre-endovascular era (pre-EA)' January 2013–January 2015 and 'endovascular era (EA)' February 2015– December 2016). We calculated the proportion of AIS admissions in which, first, VT and second, ET was performed. Among patients treated with ET, we examined the association between era and discharge disposition, in-hospital mortality during index admission, and 30-day readmission. Results: There were 925 363 index AIS admissions before the EA and 857 347 during. A higher proportion of AIS patients received IVT (8.4% vs 7.8%) and ET (2.6% vs 1.3%) in the EA. Although length of stay (LOS) was shorter in the EA (5.70 vs 6.80 days), total charges were greater (56 691 vs 53 878), and admissions were more often to a metropolitan hospital (65.2% vs 57.2%). Among those treated with ET, a smaller proportion received IVT (29.7% vs 44.9%), LOS was substantively shorter (9.75 vs 12.76 days), and patients had a lower odds of discharge home. Conclusions: The utilization of ET has doubled in the EA but ET remains underutilized. ET is predominantly provided at metropolitan teaching hospitals and associated with higher charges despite shorter LOS and unchanged in-hospital mortality.